#TITLE_ALTERNATIVE# - NURBANI
In 2005-2009 strategic planning of the Indonesian Education Department, government has scheduled an ICT implementation on education in primary school, such as: to design and to implement web based application, interactive multimedia, that consist of an application on tutorial and learning tool. For example, e-learning application with both internet and intranet in it. E-learning application can be used to change conventional ways to digital learning process, provide it highly interactive and convenient. The interactive aspect in learning is merely required to be implemented to enrich creativity and independent. To create learning are more convenient, any course and training material can be delivered by using animation and game technology. If learning and game are combined, it will make a something new and better. Those two words do no have any exclusively relationship obviously, by using the most appropriate design and tools, it can be performed well in good correlation. Mathematics for standard three primary school students is considered as case study in this thesis. As a reason that lesson need to be given to all student from primary school acknowledge them a logical thinking, analytical, systematic, critical, creative and cooperative ability. CTL is used to have a learning approach in this thesis. The pupose that can help students to understood about meaning of a lesson and apply it in their daily activities. Hence, they will have flexible knowledge to be applied in according of context to another. Pedagogic and technology substance are used in arranging this thesis, as theory of curriculum, CTL, e learning, game and animation. Then next steps are analysis of system, LMS, content and game designing, implementation, and test system. It's hope that through the various created facilities in this application, the teaching and learning process will more be attractive and convenient. So, that student will highly be easily to understand any concept of each material, providing effective and efficient learning process. Meanwhile, the developed application will support ICT implementation on education and an interaction system among students and subject teacher.